Design, implementation, and demographic differences of HEAL: a self-report health care leadership instrument - Murphy KR; McManigle JE; Wildman-Tobriner BM; Little Jones A; Dekker TJ; Little BA; Doty JP; Taylor DC (Dove Medical Press, 2016)
Kelly R Murphy, John E McManigle, Benjamin M Wildman-Tobriner, Amy Little Jones, Travis J Dekker, Barrett A Little, Joseph P Doty, Dean C Taylor Duke Healthcare Leadership Program, Duke University School of Medicine, Durham, NC, USA Abstract: The medical community has recognized the importance of leadership skills among its members. While numerous leadership assessment tools exist at present, few are specifically tailored to the unique health care environment. The study team designed a 24-item survey (Healthcare Evaluation & Assessment of Leadership [HEAL]) to measure leadership competency based on the core competencies and core principles of the Duke Healthcare Leadership Model. A novel digital platform was created for use on handheld devices to facilitate its distribution and completion. This pilot phase involved 126 health care professionals self-assessing their leadership abilities. The study aimed to determine both the content validity of the survey and the feasibility of its implementation and use. The digital platform for survey implementation was easy to complete, and there were no technical problems with survey use or data collection. With regard to reliability, initial survey results revealed that each core leadership tenet met or exceeded the reliability cutoff of 0.7. In self-assessment of leadership, women scored themselves higher than men in questions related to patient centeredness (P=0.016). When stratified by age, younger providers rated themselves lower with regard to emotional intelligence and integrity. There were no differences in self-assessment when stratified by medical specialty. While only a pilot study, initial data suggest that HEAL is a reliable and easy-to-administer survey for health care leadership assessment. Differences in responses by sex and age with respect to patient centeredness, integrity, and emotional intelligence raise questions about how providers view themselves amid complex medical teams. As the survey is refined and further administered, HEAL will be used not only as a self-assessment tool but also in “360” evaluation formats. Keywords: emotional intelligence, patient centeredness, sex, specialty, age, leadership assessment